Whole genomewide linkage screen for neural tube defects reveals regions of interest on chromosomes 7 and 10. Issue 12 (14th April 2005) - Rampersaud, E; Bassuk, A G; Enterline, D S; George, T M; Siegel, D G; Melvin, E C; Aben, J; Allen, J; Aylsworth, A; Brei, T; Bodurtha, J; Buran, C; et al.
Abstract : Neural tube defects (NTDs) are the second most common birth defects (1 in 1000 live births) in the world. Periconceptional maternal folate supplementation reduces NTD risk by 50–70%; however, studies of folate related and other developmental genes in humans have failed to definitively identify a major causal gene for NTD. The aetiology of NTDs remains unknown and both genetic and environmental factors are implicated. We present findings from a microsatellite based screen of 44 multiplex pedigrees ascertained through the NTD Collaborative Group. For the linkage analysis, we defined our phenotype narrowly by considering individuals with a lumbosacral level myelomeningocele as affected, then we expanded the phenotype to include all types of NTDs. Two point parametric analyses were performed using VITESSE and HOMOG. Multipoint parametric and nonparametric analyses were performed using ALLEGRO. Initial results identified chromosomes 7 and 10, both with maximum parametric multipoint lod scores (Mlod) >2.0. Chromosome 7 produced the highest score in the 24 cM interval between D7S3056 and D7S3051 (parametric Mlod 2.45; nonparametric Mlod 1.89). Further investigation demonstrated that results on chromosome 7 were being primarily driven by a single large pedigree (parametric Mlod 2.40). When this family was removed from analysis, chromosome 10 was the most interesting region, with a peak Mlod of 2.25 at D10S1731. Based on mouse human synteny, two candidate genes ( Meox2, Twist1 ) were identified on chromosome 7. A review of public databases revealed three biologically plausible candidates ( FGFR2, GFRA1, Pax2 ) on chromosome 10. The results from this screen provide valuable positional data for prioritisation of candidate gene assessment in future studies of NTDs.